Characterization and Purification of Membrane‐Bound Azoreductase From Azo Dye Degrading Shewanella sp. Strain IFN4. Issue 11 (31st August 2016) - Imran, Muhammad; Negm, Fayek; Hussain, Sabir; Ashraf, Muhammad; Ashraf, Muhammad; Ahmad, Zulfiqar; Arshad, Muhammad; Crowley, David E.
Abstract : Azo dyes can be degraded by azoreductases that achieve initial decolorization of the dye molecule through cleavage of the azo bond. Here we characterized membrane‐bound azoreductase enzyme expressed by Shewanella sp. strain IFN4, which is a particularly efficient azo dye degrading bacterium. Initial studies showed that this bacterium was capable of decolorizing a wide variety of azo dyes including Reactive Black 5, Acid Red 88, Direct Red 81, Acid Yellow 19, and Disperse Orange 3. These structurally different azo dyes were also found to be reduced by the membrane‐bound azoreductase showing the wider substrate specificity of the enzyme. Maximum enzyme activity was observed at pH 8 and 45°C with Reactive Black 5 as a substrate, and was stimulated on the addition of flavin or quinone compounds. The azoreductase was partially purified using a combination of ammonium sulfate precipitation followed by anion exchange chromatography. The cell membrane azoreductase was identified by non‐denaturing gel electrophoresis and was shown to have a molar mass of 33 ± 0.5 kDa. Analysis of protein fragments by mass spectrometry showed high similarity with a Na(+)‐translocating NADH‐quinone reductase, previously identified in different species of the genus Shewanella . This enzyme is the first to be identified as a primary functional membrane‐bound azoreductase used by members of the genus Shewanella to degrade azo dyes. Abstract : A membrane‐bound azoreductase is purified using a combination of ammonium sulfate precipitation followed by anion exchange chromatography. This enzyme is identified as a primary functional membrane‐bound azoreductase used by members of the genus Shewanella to degrade azo dyes for the first time. The enzyme has broad substrate specificity and can decolorize azo dyes over a range of pH and temperature.